IDENTIFIKASI DAN PENETAPAN KADAR RHODAMIN B PADA KUE BERWARNA MERAH DI PASAR ANTASARI KOTA BANJARMASIN - Ratih Pratiwi Sari (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Rhodamine B is a synthetic dye used to dye the textile industry. Rhodamine B is presence in food can cause poisoning, skin irritation, lung irritation, eye irritation, throat irritation, nasal irritation, and cause liver damage if exposed to high concentrations. Samples taken from the red cake seller in the Antasari Banjarmasin market. This research is a descriptive study. The sampling technique used was accidental sampling. Rhodamine B on a method of identification of samples using Thin Layer Chromatography and Visible spectrophotometry. Samples were prepared using the absorption method wool. The resulting solution will be used as identification in Thin Layer Chromatography using silica gel GF 254 plates with a mobile phase of n-butanol : ethyl acetate : ammonia (10:4:5). Rhodamine B assay performed visible spectrophotometry at a wavelength of 544 nm.Results of identification were putri ayu cake, Apam cake, Kukus cake A, Bolu cake, Singkong cake, and Kukus cakes B, shows that 1 positive samples containing Rhodamine B is a Apam cake. After that, the assay of Rhodamine B was performed in the sample apam cake and obtained for 0,4229 ± 0,1157 mg of Rhodamine B in 1 piece of red cake